IMPLEMENTASI PROGRAM 3R (REDUCE, REUSE DAN RECYCLE) PERATURAN DAERAH KOTA PEKANBARU NOMOR 08 TAHUN 2014 TENTANG PENGELOLAAN SAMPAH DI TAMAN KOTA PEKANBARU - Shindy Fauziyah; Maria Maya Lestari; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
This research focuses on the implementation of the 3R (Reduce, Reuse, and Recycle)programme in Pekanbaru City Regional Regulation Number 08 of 2014 concerning WasteManagement in Pekanbaru City Parks. The 3R programme is the government's effort toovercome the waste problem which is one of the biggest problems in the environment ofPekanbaru city. The goal is to reduce the amount of waste, foster public awareness, andprovide benefits for community empowerment. This research examines the extent of publicawareness in implementing the 3R programme and how the government supports theprogramme in public places such as city parks in accordance with applicable regionalregulations.This type of research is sociological research and descriptive in nature. The researchlocation was conducted in 4 locations, namely the Pekanbaru City Environment and HygieneOffice, Pekanbaru Mayang Glass Park, Pekanbaru Tunjuk Integritas Park, and PekanbaruCity Park. The population of this research is park visitors and parties related to parkmanagement in Pekanbaru City. Samples were taken by simple randomisation from thepopulation of park visitors. Data sources consist of primary data through observation,interviews, and questionnaires to the government, related agencies, janitors, and visitors tocity parks. Secondary data is obtained from laws and regulations, books, and previous researchresults. Data collection techniques were carried out through observation, interviews,questionnaires, and document studies. Data analysis uses qualitative analysis by describingand interpreting data and drawing conclusions deductively.From the results of the study it can be concluded that public awareness in implementingthe 3R Programme in Pekanbaru City Park is still lacking. There are still many visitors whothrow garbage not in the place that has been provided. In addition, the lack of personal hygieneofficers also affects the running of the 3R programme in Pekanbaru City Park. Second, theimplementation of the Pekanbaru City Regional Regulation number 8 of 2014 concerningWaste Management in Pekanbaru City, on the Communication indicator in the implementationof waste management in Pekanbaru related to socialisation, the value is not yet optimal but theagency will make maximum efforts to provide understanding to the public about the impact ofthe dangers of littering, secondly on the Resource indicator related to the lack of personnel inwaste management due to the limited budget owned by the agency. However, in the nextindicator, the role of the government has been carried out well.Keywords: Implementation, 3R Program, PERDA.